Novel Anaplasma (Rickettsiales: Anaplasmataceae) strain and Hepatozoon sp. cf. H. procyonis (Apicomplexa, Hepatozoidae) detected in Procyon cancrivorus (Carnivora, Procyonidae) from Argentina, with note of tick-host association - Tarragona, Evelina Luisa; Sebastian, Patrick; Félix, Maria L.; Venzal, José Manuel (Springer, 2024)
The aim of this work is to report the first detection of Procyon cancrivorus naturally co-infected with Hepatozoon sp. cf. H. procyonis and a novel Anaplasma strain from South America and potential vector tick species associated. On August 30, 2016, a specimen of P. cancrivorus was found dead on the route in Chaco province, Argentina. A tick and a blood sample by cardiac puncture was collected from the specimen. DNA was extracted from blood sample and the tick was morphological identity as a female of Amblyomma ovale. Molecular detection of Anaplasmataceae family and Hepatozoon spp. agents was performed targeting two different loci: 16 S rRNA and 18 S rRNA gene. The phylogenetic analyses show that the Anaplasma sp. strain detected in P. cancrivorus in this study is similar to Anaplasma sp. strains previously detected in Nasua nasua and A. ovale from Brazil. Furthermore, Hepatozoon sp. of the H. procyonis group was amplified that is phylogenetically closely related to H. procyonis reported in N. nasua from Brazil. Since it was not exactly the same as the latter, it was decided to name at Hepatozoon sp. cf. H. procyonis. It is possible that, this potential new species of Anaplasma would be specific for Procyonidae family and there are two species of Hepatozoon linked to this family in South America. These results added to other published studies suggest that A. ovale could be a potential vector both for the new potential strain of Anaplasma and for the Hepatazoon sp. of the H. procyonis group.